The role of SPINK5 mutation distribution in phenotypes of Netherton syndrome - Min Xu; Yujie Shi; Li Lin; Liang Wang; Xianzhong Zhu; Jinglin Xiong; Jiawen Yin; Qing Qi; Wenlin Yang (Frontiers in Genetics)
ObjectiveNetherton syndrome (NS) is a rare hereditary dermatosis, and the correlation between genotype and phenotype in this disease warrants further investigation. This study aimed to explore the genotype-phenotype correlation in NS.MethodsWe collect cases from our clinic and relevant literature. After rigorous screening, we included 162 patients with NS-associated symptoms and SPINK5 mutations. We characterized the distribution and mutation types of allele variants. Logistic regression was employed to analyze the correlation between the location of these variants and phenotypes. Additionally, the association between the homozygous condition of variants and death during infancy was analyzed using the Chi-square test.ResultsAmong 162 patients, we identified 324 allele variants, comprising 75 different mutations. Of these, 73 patients carried heterozygous variants, while 89 patients had homozygous variants. We observed that patients with variants or homozygous variants located in the 5′ half of the gene were more likely to experience failure to thrive (P < 0.05). Similarly, variants or homozygous variants located outside DomainR-5 were also associated with an increased risk of failure to thrive (P < 0.05). Furthermore, variants in domain regions were significantly correlated with the presence of ichthyosis linearis circumflexa (P < 0.01). Patients with homozygous fatal variants (c.153delT, c.1431-12G>A, c.1111C>T, c. 1887 + 1G>A, and c. 995delT) had a higher likelihood of mortality during infancy (P < 0.001).ConclusionOur study provides valuable insights into the genotype-phenotype correlation in Netherton syndrome, enhancing our understanding of the disease and potentially informing the development of future therapeutic approaches.